2015
DOI: 10.4103/0975-9476.172382
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a polyherbal formulation in hemorrhoids

Abstract: Background:The medical management of hemorrhoids should include an integrated approach. This integrated approach can be achieved by polyherbal formulations containing anti-inflammatory, styptics, analgesics, and laxative effect which reduce inflammation, pain, and bleeding, and increase gastro-intestinal motility and soften stools. One such polyherbal kit is “Arshkeyt™, a 7 day kit,” which consists of oral tablets and powder along with topical cream.Objective:Efficacy and safety of Arshkeyt™, a 7 day kit, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In this study, a combination of Arsha Hita tablets and Arsha Hita ointment was found to be an effective initial treatment option for anal fissures that doesn't require surgery. The tablets contain ingredients such as Arishtak (Sapindus trifoliatus) and Soorana (Amorphophallus campanulatus), which have anti-inflammatory properties, while Sarja (Vateria indica) helps with wound healing [4][5][6]. The Arsha Hita ointment used in the study contains Tila Taila or Sesame oil, which is known for its wound healing and analgesic properties.…”
Section: Secondary Endpointsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a combination of Arsha Hita tablets and Arsha Hita ointment was found to be an effective initial treatment option for anal fissures that doesn't require surgery. The tablets contain ingredients such as Arishtak (Sapindus trifoliatus) and Soorana (Amorphophallus campanulatus), which have anti-inflammatory properties, while Sarja (Vateria indica) helps with wound healing [4][5][6]. The Arsha Hita ointment used in the study contains Tila Taila or Sesame oil, which is known for its wound healing and analgesic properties.…”
Section: Secondary Endpointsmentioning
confidence: 99%
“…Arishtak and Soorana have been specifically noted for their anti-inflammatory actions. Sarja, on the other hand, contributes to the wound-healing action [4][5][6]. On the other hand, Arsha Hita ointment is formulated with Tila Taila or sesame oil (Sesamum indicum), which has wound-healing and analgesic properties [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the true burden of disease is difficult to capture as many patients are reluctant to seek medical suggestions for various personal, cultural, and socio-economic reasons [ 2 , 6 , 7 ]. The prevalence of hemorrhoids in India according to recent surveys is around 40 million [ 8 ]. Several risk factors have been claimed to be the etiologies of hemorrhoid development including aging, obesity, depression, pregnancy, chronic constipation and diarrhea, low-fiber diet, spicy foods, and alcohol intake [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the true burden of disease is difficult to capture as many patients are reluctant to seek medical suggestions for various personal, cultural, and socio-economic reasons [2,6,7]. The prevalence of hemorrhoids in India according to recent surveys is around 40 million [8]. Several risk factors have been claimed to be the etiologies of hemorrhoid development including aging, obesity, depression, pregnancy, chronic constipation and diarrhea, lowfiber diet, spicy foods, and alcohol intake [9].…”
Section: Introductionmentioning
confidence: 99%